Effect of Predigested Artificial Diet Using Papain Enzyme on the Degree of Protein Hydrolysis and Protease Enzyme Activity of Mud Crab (Scylla olivacea) Larvae at Zoea 2 and 3 Stages - Haryati, Haryati; Fujaya, Yushinta; Saade, Edison (Indonesian Aquaculture Society (MAI), 2018)
The ability of mud crab (Scylla olivacea) larvae to digest artificial diet depends on the availability of digestive enzyme. To enhance the larvaes capability to utilize artificial diet can be conducted by adding exogenous enzyme to the diet.The aim of this research was to determine the dose of papain enzyme and stadia of predigest artificial diet that produced the best degree of protein hydrolysis and protease enzyme activity. Completely randomized designwas used to evaluate the effect of papain enzyme dose on the degree of protein, with four treatment and three replications, namely the doses of 0.0%, 1.5%, 3.0%, and 4.5%. Factorial pattern with the completely randomized design was used to evaluate the effect of papain enzyme dose and the proper predigest artificial feeding stage on the activity of protease enzyme. The first factor was the papain enzyme dose (0.0%, 1.5%, 3.0%, and 4.5%), while second factor was the stadia of larvae when it is fed with predigested artificial diet (zoea 2 and zoea 3 stadia). The research showed that the difference of papain enzyme dose provides real effect on degree of protein hydrolysis either on JP 0 or JP 1 diet brands (P<0.05). Degree of protein hydrolysis of the diet predigested with 0.0% papain enzyme was the lowest and has real difference (P<0.05) with the 1.5%, 3.0% and 4.5% doses. Degree of protein hydrolysis on 3% dose of papain enzyme does not provide real difference with the 4.5%, namely 19.753% and 22.890% respectively in JP 0, 18.707 % and 20.430 % in JP 1, but has real difference (P<0.05) with 1.5% doses. The difference papain enzyme dose and stadia of predigest artificial diet as well as the interaction between both of them had significant effect (p<0.05) on the activity of protease enzyme. On the larvae of zoea 2 stadia, the activity of protease enzyme on the larvae fed with predigest artificial diet starting from zoea 2 stadia with 3.0% and 4.5% papain enzyme dose or those still fed with natural diet does not provide real difference, but is higher and provides real difference than 0% and 1.5% doses. On the larvae of zoea 3 stadia, the activity of protease enzyme to the larvae fed with artificial diet starting from zoea 2 with 0% and 1.5% papain enzyme doses, and those fed with artificial diet starting from zoea 3 stadia with 0% papain enzyme dose does not provide real difference (p>0.05) but is lower and provides real difference than other treatments. Protease enzyme activity on the larvae fed with predigest artificial diet using 4.5% papain enzyme starting at zoea 2 stadia , was not significantly different (P <0.05) compared to larvae fed artificial diet which was predigest with 0.0%, 1.5%, 3.0 and 4.5 papain enzyme started at Zoea 3. Based on the degree of protein hydrolysis, papain enzymes can be used to hydrolyze artificial diet in doses ranging from 3.0% to 4.5%. Based on the activity of protease enzymes, mud crab larvae (Scylla olivacea) predigested artificial diet using 4.5% papain enzyme can be provided to the larvae starting from zoea 2 stadia.